Insilico, Synthesis and Invitro Evaluation of Novel Thiadiazoles as Inhibitors Caspase 3 For Potential of Anticancer - Jahnavi, Patibandla.; Tiwari, Gaurav; Rajendiran, A; Patwekar, Varsha; Baburao Rode, Ramdas; Ashwini Ashok, Jamdhade; Priya E S, Sindhu; R, Praveencumar (Journal of Neonatal Surgery, 2025)
This paper explains how to create different new compounds that include thiadiazole and imidazole with a cyclopropyl group. The diverse biological activities and therapeutic applications of imidazothiadiazoles render them intriguing. We predominantly perform docking experiments using the reference structure PDB ID 3KJ7. To focus on the cysteine proteases in the caspase family, we have created a new group of diaryl compounds that have imidazothiadiazoles attached. To monitor the reaction, we employed thin-layer chromatography with an appropriate mobile phase. By comparing the Rf values, the melting point of the produced compounds was ascertained. To further characterize and validate these derivatives, we used mass spectrometry analyses, one-dimensional nuclear magnetic resonance, carbon-13 nuclear magnetic resonance, and infrared spectroscopy. All cancer cell lines were effectively inhibited by compounds 1 and 3. The manufactured medications were assessed using a colorimetric assay using a caspase 3 inhibitor kit.